The Effect of Accounting Competencies, Information Systems, and Compliance on the Quality of MSME Financial Reporting through Accountability - Antoni, Antoni (Westscience Press, 2025)
This study examines the influence of accounting competencies, information systems, and compliance on the quality of financial reporting in Micro, Small, and Medium Enterprises (MSMEs) with accountability as a mediating factor. Employing a quantitative approach, data were collected from 130 MSME respondents using a Likert-scale questionnaire (1–5). The analysis utilized Structural Equation Modeling–Partial Least Squares (SEM-PLS 3). The results reveal that accounting competencies, compliance, and information systems each have a significant positive effect on financial reporting quality. Compliance emerged as the strongest predictor, emphasizing the importance of adhering to regulations and standards in enhancing reporting credibility. Furthermore, the combined effect of these factors explained 71.8% of the variance in financial reporting quality, underscoring the integrated role of human resources, institutional legitimacy, and technological adoption. This study contributes both theoretically and practically by providing insights into strengthening MSME financial governance through improved competencies, compliance culture, and digital system utilization.